A search for massive resonances in final states with boosted top-antitop pairs decaying into a lepton and jets with the ATLAS detector at the Large Hadron Collider - Behr, J (2015)
In this thesis, a search for new elementary particles decaying to a top-antitop pair (ttbar) is presented. Massive new particles that preferentially decay to top quarks are predicted by a number of theoretical models that have been proposed to address various open questions in the currently established Standard Model of Particle Physics, in particular those related to the Higgs mechanism through which elementary particles acquire mass. The search is conducted in proton-proton collision data collected by the ATLAS experiment at the Large Hadron Collider, located at CERN, the European Laboratory for Particle Physics. The integrated luminosity of the dataset, which was collected in 2012, is 20.3 fb-1 . This is the first and only search for new particles in ttbar final states that uses the full ATLAS dataset collected in collisions at the centre-of-mass energy √<em.s< em=""> = 8 TeV.</em.s<> The search focuses on ttbar-->(Wb)(Wbbar) final states in which one W boson decays into an electron or muon and the corresponding (anti)neutrino and the other W boson decays into a quark and an antiquark. The detector signature of these events is characterised by the presence of an electron or muon, a certain number of hadronic jets and large missing transverse energy. Two independent reconstruction strategies for top quarks with small and large transverse momenta, respectively, are combined to optimise the sensitivity of the search over the mass range between 0.4 TeV and 3.0 TeV. In particular, jet substructure techniques as well as a transverse- momentum dependent treatment of lepton isolation and lepton-jet overlap are used to account for the collimation of the decay products of highly energetic (boosted) top quarks. The distributions of the reconstructed ttbar invariant mass in data are analysed for local excesses or deficits with respect to the Standard Model prediction. No evidence for the existence of new particles is found in the analysed mass range. Upper limits on the cross-section times branching ratio to ttbar , at the 95% confidence level, are derived for four benchmark models. For a narrow Z' resonance, these limits range from 4.2 pb for a resonance mass of 0.4 TeV to 0.03 pb for a mass of 3.0 TeV. A topcolor-assisted technicolor Z'TC2 boson with a relative width of 1.2% is excluded for masses between 0.4 TeV and 1.8 TeV. Upper limits on the cross-section times branching ratio of 4.8 pb (0.09 pb) at 0.4 TeV (3.0 TeV) are also derived for a broad colour-octet state with a width of 15.3%. A Bulk RS Kaluza-Klein gluon with the above width is excluded in the mass range between 0.4 TeV and 2.2 TeV. For the first time in ATLAS, the results of a resonance search in ttbar final states are also interpreted in the context of models with a narrow Bulk RS Kaluza-Klein graviton and a generic scalar resonance, respectively. The upper limits on the cross-section times branching ratio for the Bulk RS Kaluza-Klein graviton (scalar resonance) range from 2.5 pb (3.0 pb) at 0.4 TeV to 0.03 pb at 2.5 TeV (3.0 TeV).